Motivating foreign students' learning based on their reading skills: the example of foreign students studying in Inner Mongolia Autonomous Region of China - Yanjiang, Li; Alimaa, Tuya; Qingaowa, Si; Khujuu, Tamir; Bekhbaatar, Batsaikhan; Yaish, Shiilegmaa (Lavai - International Journal of Education, 2024)
This study examines the reading comprehension skills of foreign students to identify the factors that influence their ability to read in a foreign language. A total of 174 Mongolian students from universities in the Inner Mongolian Autonomous Region of China have been participated in a questionnaire survey to assess their reading abilities. Among the participants, 70.1% were found to have an intermediate level of Chinese language proficiency, suggesting that the findings of this study are credible, as the participants represent a homogeneous proficiency group. While these students self-assessed their Chinese reading ability at 81.61%, actual results varied. Specifically, 54.2% reported difficulties with scientific texts, 32.18% found literary works challenging, and 31.03% struggled with newspaper articles. These findings suggest that insufficient knowledge of scientific vocabulary is a major impediment to improving overall reading ability.